Laser-Synthesis of NV-Centers-Enriched Nanodiamonds: Effect of Different Nitrogen Sources - Luca Basso; Mirko Sacco; Nicola Bazzanella; Massimo Cazzanelli; Alessandro Barge; Michele Orlandi; Angelo Bifone; Antonio Miotello (Micromachines, 2020)
Due to the large number of possible applications in quantum technology fields—especially regarding quantum sensing—of nitrogen-vacancy (NV) centers in nanodiamonds (NDs), research on a cheap, scalable and effective NDs synthesis technique has acquired an increasing interest. Standard production methods, such as detonation and grinding, require multistep post-synthesis processes and do not allow precise control in the size and fluorescence intensity of NDs. For this reason, a different approach consisting of pulsed laser ablation of carbon precursors has recently been proposed. In this work, we demonstrate the synthesis of NV-fluorescent NDs through pulsed laser ablation of an N-doped graphite target. The obtained NDs are fully characterized in the morphological and optical properties, in particular with optically detected magnetic resonance spectroscopy to unequivocally prove the NV origin of the NDs photoluminescence. Moreover, to compare the different fluorescent NDs laser-ablation-based synthesis techniques recently developed, we report an analysis of the effect of the medium in which laser ablation of graphite is performed. Along with it, thermodynamic aspects of the physical processes occurring during laser irradiation are analyzed. Finally, we show that the use of properly N-doped graphite as a target for laser ablation can lead to precise control in the number of NV centers in the produced NDs.